Medium term economic strategy paper May 1990 (Govt. of the Commonwealth of Dominica [Roseau]DM, 1998)
Seeks to formulate a set of consistent policies which will support the restoration of the economy to a stronger and sustainable growth path based on a more diversified productive base and stronger public finances.
DC